1992
DOI: 10.1021/ed069p909
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethanes: A class of modern versatile materials

Abstract: The myriad applications of polyurethane coatings, foams, fibers, moldings, and elastomers demonstrate the versatility of urethane chemistry and the creativity of polymer scientists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(67 citation statements)
references
References 2 publications
0
63
0
1
Order By: Relevance
“…Polyurethanes were first discovered by Otto Bayer and his colleagues in 1937 (Seymour and Kauffman, 1992). PUs are known for their wide range of properties including high tensile strength, abrasion resistance, and chemical resistance (Saraf andGlasser, 1984, Sarkar andAdhikari, 2001).…”
Section: Polyurethane (Pu)mentioning
confidence: 99%
“…Polyurethanes were first discovered by Otto Bayer and his colleagues in 1937 (Seymour and Kauffman, 1992). PUs are known for their wide range of properties including high tensile strength, abrasion resistance, and chemical resistance (Saraf andGlasser, 1984, Sarkar andAdhikari, 2001).…”
Section: Polyurethane (Pu)mentioning
confidence: 99%
“…They are applied as automotive parts, in building and construction, in electrical and engineering applications, in the oil, chemical and food industry and in many other fields [1,2]. One of their major application areas is health care, where they are used mainly as medical devices in the form of encapsulants for hollow-fiber devices, dip-molded gloves and balloons, asymmetric membranes, functional coatings, and as extruded profiles for cardiovascular catheters [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Fully reacted polyurethane polymer is chemically inert. 2 We conducted an in vitro experiment by mixing the two liquids which the patient had consumed. We found that it expanded 30 times its initial volume over a period of 3 minutes, became hard and took the shape of the container used (Figure 4).…”
Section: Discussionmentioning
confidence: 99%